FORMULATION OF CANNA STARCH AND TAPIOCA ON WATER CONTENT, ELASTICITY AND SENSORY PROPERTIES OF MACKEREL FISH PEMPEK - Widratul Faszrah; Sussi Astuti; Erdi Suroso; Novita Herdiana (Jurusan Perikanan dan Kelautan, 2026)
The study aims to determine the effect of ganyong and tapioca starch formulations on water content, elasticity and sensory properties of mackerel fish pempek, and to determine the best formulation of ganyong and tapioca starch with water content, elasticity and sensory properties of pempek that meet SNI 7661:2019. This study used a single factor RAKL and 4 replications. The research treatments were tapioca and ganyong starch formulations with a ratio of 100%: 0% (P0), 90%: 10% (P1), 80%: 20% (P2), 70%: 30% (P3), 60%: 40% (P4), and 50%: 50% (P5). Data were analyzed using variance (ANARA) and continued with the Least Significant Difference Test (LSD) at a level of 5%. The results showed that the formulation of tapioca and ganyong starch affected the water content, hardness, springiness, cohesiveness, color, aroma, taste, texture and overall acceptance of mackerel fish pempek. The treatment of 10% ganyong starch and 90% tapioca produced the best mackerel fish pempek according to SNI 7661:2019 with a color score of 6.94 (yellowish white), aroma 7.20 (typical pempek), taste 6.66 (typical pempek), texture 6.87 (chewy), overall acceptance 7.39 (like), water content of 51.45%, protein content of 18.39%, hardness value of 244.77 N, springiness value of 7.97 mm, and cohesiveness value of 0.63 N.